Bridging the Effect of the Impactor Head Shape to the Induced Damage during Impact at Low Velocity for Composite Laminates - Rabouh, Mustapha; Guerraiche, Khelifa; Zouggar, Kamel; Guerraiche, Djemaa (Engineering, Technology & Applied Science Research, 2023)
The present paper presents an investigation and analysis study of the effect of the head shapes of the impactor on the damages observed during low-velocity impact on T700/Epoxy composite laminate. Two types of impactors were investigated: hemispherical and flat-face. A new criterion based on the LARC05 damage model was linked as a LARC_VUMAT subroutine to simulate the impact and explore the effects of the head form shape through a three-dimensional finite element model. To properly analyze the problem, the history time of the mechanical responses, such as impact forces, bending, principal, and residual stresses, are highlighted and assessed. Additionally, a comparison with the experimental data found in the literature was performed to check the validity and accuracy of the considered finite element model. The damage occurring in the T700/Epoxy plates is illustrated for each impactor head shape. The mechanical response curves and all kinds of damage of the presented simulations are in perfect agreement with the experiments. The proposed VUMAT is efficient in the prediction of fiber kinking, matrix cracking, fiber splitting, and fiber tension of a laminate, and more importantly, it is easy to implement for other types of materials and the reproducibility of the analysis is assured.